Surgical outcomes of Hemivertebra Resection with Mono-Segment Fusion in Children under 10 years with congenital scoliosis: a retrospective study stratified by the Crankshaft Phenomenon - Zhiming Peng; You Du; Haoran Zhang; Bingtai Han; Shengru Wang; Jianguo Zhang (BMC Musculoskeletal Disorders)
Abstract Background Congenital early-onset scoliosis (CEOS), particularly due to hemivertebra, presents significant challenges in spinal deformity correction. The standard surgical approach, hemivertebra resection combined with short-segment fusion, can be complicated by the crankshaft phenomenon, a progressive deformity that may develop postoperatively. This study aims to evaluate the long-term surgical outcomes of single-stage posterior hemivertebra resection with mono-segment fusion in CEOS, stratified by the presence or absence of the crankshaft phenomenon. Methods A retrospective analysis was performed on 31 CEOS patients who underwent single-stage posterior hemivertebra resection and mono-segment fusion between 2003 and 2019. Patients were grouped based on the presence (n = 9) or absence (n = 22) of the crankshaft phenomenon. Clinical and radiographic outcomes, including main curve correction, compensatory curves, apical vertebral translation (AVT), coronal balance (CB), and sagittal balance (SB), were assessed at preoperative, immediate postoperative, and latest follow-up points. Statistical analyses were performed using SPSS and R software. Results The cohort showed significant deformity correction with an initial main curve angle reduction from 29.76° to 7.34° (76% correction rate), though some loss of correction was observed at the last follow-up (12.28°). The group with the crankshaft phenomenon exhibited a significantly lower initial correction rate (62%) compared to the non-crankshaft group (82%), with a higher rate of curve progression at follow-up (25.02° vs. 7.06°). Compensatory curves, AVT, and CB showed differences between groups, with those having the crankshaft phenomenon demonstrating worse outcomes. However, no significant differences were found in sagittal parameters (segmental kyphosis, thoracic kyphosis, and lumbar lordosis) between the two groups. Conclusions The study demonstrates that single-stage posterior hemivertebra resection with mono-segment fusion is effective in correcting deformities in CEOS patients. However, the presence of the crankshaft phenomenon is associated with a poorer long-term surgical outcome, including higher rates of curve progression and worse compensatory curve management. These findings highlight the importance of identifying the crankshaft phenomenon as a potential factor influencing the prognosis of surgical correction in CEOS.